2000
DOI: 10.1292/jvms.62.361
|View full text |Cite
|
Sign up to set email alerts
|

Serum Parathyroid Hormone and Calcitonin Levels in Racehorses with Fracture.

Abstract: . Serum parathyroid hormone (PTH) and calcitonin (CT) levels in fractured racehorses were measured by radioimmunoassay. Racehorses with fracture of large bone such as the radius, third metacarpus, third carpus, digital bone or tibia, showed normal PTH level and elevated CT level in the serum. Serum PTH level was slightly higher in racehorses with sesamoid bone fracture compared to that of healthy racehorses, but not statistically significant. Moreover, serum CT level of racehorses with sesamoid bone fracture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…But the group with a distal bone fracture had a remarkably and statistically higher number of C cells (P<0.01) at the time of bone fracture than the groups with fractures at other sites. In the case of fracture of the lateral proximal s esamoid, changes in the blood concentrations of parathyroid gland hormone and calcitonin were found to differ, suggesting that calcitonin adjustment was different at the time of fracture of a large bone and the lateral proximal sesamoid [1,8]. In the present study, comparison of the number of previous races with the number of C cells in 131 racehorses revealed that 2-year, 3-year and 4-year-old racehorses had a tendency for an increase in the number of C cells with an increase in the frequency of races.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…But the group with a distal bone fracture had a remarkably and statistically higher number of C cells (P<0.01) at the time of bone fracture than the groups with fractures at other sites. In the case of fracture of the lateral proximal s esamoid, changes in the blood concentrations of parathyroid gland hormone and calcitonin were found to differ, suggesting that calcitonin adjustment was different at the time of fracture of a large bone and the lateral proximal sesamoid [1,8]. In the present study, comparison of the number of previous races with the number of C cells in 131 racehorses revealed that 2-year, 3-year and 4-year-old racehorses had a tendency for an increase in the number of C cells with an increase in the frequency of races.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the blood calcitonin level is significantly increased in racehorses with a bone fracture relative to the level in healthy horses [1]. But there has been no pathological research conducted on the morbidity of thyroid gland C cells, which play a role in bone metabolism and in the formation of the lesion causing the fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pony was referred to Obihiro University in spring 2003 because of astasia and fractures of the forelegs and hind legs and showed clinical signs (miscarriage, bone fractures) and pathological signs (swollen parathyroid, bone replaced by fibrous tissue and formation of Howship's lacunae) of NSH [1][2][3][4][5]14]. The owner of the pony had at the same stable five ponies [two stallions (pony 2, 3) and three mares (pony 4-6)] and two donkeys [a stallion (donkey 1) and a mare (donkey 2)] that had also been fed a high phosphorus/low calcium diet for more than half a year and consequently were showing clinical signs (miscarriage, lameness) of NSH.…”
mentioning
confidence: 99%
“…They have revealed that exercise had changed the morphology of the third metacarpal bones [3,12,13,19,25]. Chiba et al [7] and Yoshikawa et al [24] have pointed out that the endocrine system was related to fracture in horses. Nevertheless, it was difficult to find other researches into bone disease which had been related to the endocrine systems, such as the thyroid and parathyroid.…”
mentioning
confidence: 99%